The Influence Of Discipline And Work Environment On Employee Performance At PT Smarco Mandiri Sukses - Juniarti, Juniarti; Pohan, Syahrial Hasanuddin; Bana, M. Haidir Alisyah (Universitas Dehasen Bengkulu, 2025)
Work environment on employee performance at PT Smarco Mandiri Sukses. The approach method used is a quantitative approach with a quantitative descriptive research type in the form of numbers and statistical analysis using SPSS Version 26. The population of this study is all permanent and honorary employees who work at PT Smarco Mandiri Sukses, totaling 182 employees, while the sampling technique is Probability Sampling with the technique used is Random Sampling using the Slovin formula with an error rate of 10%, so the sample of this study is 65 employees. The results of this study indicate that discipline has a positive and significant partial effect on employee performance with a calculated t value > t table (7.559 > 1.99897) and the work environment has a positive and significant partial effect on employee performance with a calculated t value > t table (6.016 > 1.99897), and simultaneously discipline and work environment have a positive and significant effect on employee performance at PT Smarco Mandiri Sukses with a calculated f value > ft table (105.821 > 3.15). The results of this study indicate that H1 is partially and simultaneously accepted and H0 is rejected. The resulting coefficient of determination is 76.6%, with the remaining 23.4% explained by other independent variables not examined in this study.